2019
DOI: 10.1101/789917
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dopamine 2 receptor signaling controls the daily burst in phagocytic activity in the mouse retinal pigment epithelium

Abstract: AbstractPurposeA burst in phagocytosis of spent photoreceptor outer fragments by retinal pigment epithelium (RPE) is a rhythmic process occurring 1-2 hours after the onset of light. This phenomenon is considered crucial for the health of the photoreceptors and RPE. We have recently reported that dopamine, via dopamine 2 receptor (D2R), shifts the circadian rhythm in the RPE.Methods… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(36 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…Interestingly, there were no differences in the total number of phagosomes engulfed in all mouse models used ( Figure 2F, one-way ANOVA, p > 0.1). We have previously reported that activation of dopamine 2 receptor (D2R) signaling is required for the presence of the diurnal phagocytic peak of photoreceptor outer segments (Goyal et al, 2020a). Thus, we decided to investigate whether removal of Bmal1 from the RPE will also affect D2R expression.…”
Section: Loss Of Bmal1 In the Rpe Dramatically Reduces The Daily Peakmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, there were no differences in the total number of phagosomes engulfed in all mouse models used ( Figure 2F, one-way ANOVA, p > 0.1). We have previously reported that activation of dopamine 2 receptor (D2R) signaling is required for the presence of the diurnal phagocytic peak of photoreceptor outer segments (Goyal et al, 2020a). Thus, we decided to investigate whether removal of Bmal1 from the RPE will also affect D2R expression.…”
Section: Loss Of Bmal1 In the Rpe Dramatically Reduces The Daily Peakmentioning
confidence: 99%
“…Whole eyes were processed for phagosome counting as previously described (Goyal et al, 2020a) and labeled with the primary rhodopsin 4D2 antibody (Abcam, ab98887). Briefly, whole eyes were fixed in 4% paraformaldehyde for at least 3 hours and transferred to 30% sucrose (Fisher, S5-500) for cryoprotection.…”
Section: Phagosome Counting Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…Intriguingly, approaches promoting POS degradation through lysosomes re-acidification within impaired RPE cells include stimulation of beta-2 adrenergic, A2A adenosine, and D5 dopamine receptors [ 118 ]. This is interesting since adenosine, norepinephrine, and dopamine, which play a role in retinal function and POS phagocytosis [ 118 , 119 , 120 , 121 , 122 ], are known to variously affect mTOR-, AMPK-, and TFEB-related autophagy and also the proteasome system through stimulation of beta-adrenergic, A2A adenosine, and D1/D2-like dopamine receptors [ 123 , 124 , 125 , 126 , 127 , 128 , 129 ]. Since autophagyā€“lysosomal dysfunction associated with either an increased activity of mTORC1 or decreased activity of AMPK or TFEB does predispose to RPE and photoreceptors degeneration in experimental models [ 36 , 97 , 129 , 130 , 131 , 132 ], it would be worth investigating whether a coupling between alterations of autophagy activity and catecholamine innervation occurs in the frame of AMD.…”
Section: Cell-clearing Systems In the Rpe As The Keys For Retinal mentioning
confidence: 99%